Kedudukan Wanita Jepang dalam Bidang Pendidikan Pada Zaman Meiji Ditinjau dari Novel Hanauzumi Karya Junichi Watanabe (Kajian Sosiologi Sastra) (Universitas Negeri Jakarta, 2017)
Literature is a person’s perspective on their view of their social surroundings, in which uses the proper language. The novel Hanauzumi was written by one of Japan’s well-known author Junichi Watanabe. It portrayed the discrimination Japanese women faced during the Meiji era. The difference between men and women in Japan’s society was caused by the practice of Ie system. According to history, the system was instated under the influence of Chinese confusionism. Initially, the Ie system only ruled over the samurais during the era of Bakufu Edo (1603-1867) ruled by Tokugawa families. But the system carried over to Meiji era (1868-1912) and was then made to govern the entire society. The system worked its way to Meiji’s base law in 1889, one of them controlled the education system that was freely opened fot both genders, although in practice, the discrimination on women still existed.